Low Baby Birth Weight (LBBW), Parity, and Perinatal Mortality in Perinatology Room of dr. M. Yunus Hospital Bengkulu - Elza Wulandari; Buyung Keraman; Rotia Amjellina (Jurnal Sains Kesehatan, 2018)
Perinatal Death is one of the events that is able to show children's health. The main causes of Perinatal death in the world include premature babies or low birth weight, sepsis, neumonía, asphyxia and trauma. This study aims to determine fatherly relationship babies of low birth weight (BBLR) and parity with perinatal mortality in hospitals Perinatology room. dr. M. Yunus Bengkulu. This study uses a case-control design. The population in this study all babies born in space Perinatology Hospital dr. M. Yunus Bengkulu in 2015. The sampling technique used total sampling to sample cases as much as 112 infants with perinatal mortality and Sytematic Random Sampling for control patients was 112 taken from 586 people perinatal infant death. Collecting data in this study using secondary data obtained from the data register the baby in the hospital midwifery perinatology. dr. M. Yunus Bengkulu.The result showed: (1) 50.0% who experienced a perinatal death as a sample of cases and 50.0% with no perinatal as a control sample; (2) 50.0% of infants born with BLR, 33.0% of infants born with BBLSR infants, and 17.0% of infants born with BBLER; (3) 42.9% of the mothers primiparous or grandemultipara and 57.1% of multiparous mothers; (4) There is a relationship between low birth weight infants (LBW) with perinatal death diruang Hospital Perinatology. dr. M. Yunus Bengkulu by category of relationship is; (5) There is a relationship between parity with hospital perinatal mortality diruang Perinatology. dr. M. Yunus Bengkulu by category of relationship is medium. Keywords: BBLR, parity, perinatal mortality